Perancangan Konfigurasi Pengendalian Proses dengan RGA pada Sistem Pure-Capacitive-Two-Tank-in-Series dengan Pemanas di Tangki T-01 - Yulius Deddy Hermawan; Siti Diyar Kholisoh; Indah Permatasari; Amy Farury Ludwinia (Seminar Nasional Teknik Kimia Kejuangan, 2016)
This research was aimed to design process control configuration in the Pure-Capacitive-Two-Tank-in-Series (PCTTS) quantitatively by using Relative Gain Array (RGA) method. Two square tanks were designed and arranged in series for investigation in laboratory. The electric heater was equipped in the tank T-01. Water was used as a fluid which is assumed that its density and heat capacity were constant. The feed water was flowed to tank T-01 and heated with an electric heater. Water of tank T-01 was then pumped to tank T-02. The pump volumetric rate can be adjusted by changing the pump voltage. This research was done through 2 procedures as follows: preliminary experiment and open loop RGA experiment. The preliminary experiment has given the steady state parameters as follows: the input and output volumetric rates of the 2 tanks were 104 cm3/second, liquid levels of tank T-01 and T-02 were 14 cm, liquid temperatures in tank T-01 and T-02 were 33.5oC, electric heat energy was 1520 watt, and pump voltage was 66.5 volt. Based on degree of freedom analysis, there were 3 variables of PCTSS system need to be controlled (CV); they were liquid temperature in tank T-01 (T1), liquid level in tank T-01 (h1), and liquid level in tank T-02 (h2). In RGA experiment, the manipulated variable candidates (MV) were changed manually based on the step function and its output (CV) responses were also be recorded. RGA calculation has resulted 3 couples of CV-MV as follows: T1-qe, h1-vpu, and h2-f2. Furthermore, study on the tuning of control parameters and closed loop simulation need to be done to examine performance of the resulted control configuration of PCCTS.